Overexpression of the mitochondrial ribosomal protein S18-2 in the invasive breast carcinomas - Buchynska, L.G.; Iurchenko, N.P.; Kashuba, E.V.; Brieieva, O.V.; Glushchenko, N.M.; Mints, M.; Lukianova, N.Yu.; Chekhun, V.F. (PH Akademperiodyka, 2018)
Summary. Background: Recent studies allow to consider the mitochondrial ribosomal protein S18-2 (MRPS18-2, S18-2) as a potential oncoprotein, which suggests the need for further characterization of its expression in tumors of different genesis including breast cancer (BC). The aim of the study was to analyze the expression of the S18-2 protein in BC of luminal A and basal subtypes. Materials and Methods: Operational material of BC patients stage І–ІІ (luminal A subtype, n = 30, and basal subtype, n = 10) was studied with the use of morphological, immunohistochemical, statistical and bioinformatic methods. Results: Using the immunohistochemical analysis, we found that the S18-2 protein showed the nuclear signal in 66.7% of luminal A subtype BC samples and 80.0% of basal subtype BC samples. The variability of the S18-2 expression in both the luminal A and basal subtypes of BC was revealed. Noteworthy, the number of cells expressing S18-2 in high-proliferating tumors of luminal A and basal subtype is significantly higher than in tumors with a low proliferative potential (p < 0.05). In 10 samples of luminal A subtype, the nuclear S18-2 signal was higher than median value. Moreover, the S18-2 protein was overexpressed in 4 out of such 10 samples. Metastases in the lymph nodes were found in 3 out of 4 patients with the stage II BC, low differentiation grade of the tumor and high proliferative activity. The bioinformatic analysis confirms our preliminary findings that the trend for increasing expression of the S18-2 protein in tumors correlates with the aggressiveness of malignant BC. Conclusion: The S18-2 protein may be a marker of cancer aggressiveness in BC patients.